Land suitability evaluation of some areas at northwestern coast {u2013} Egypt - Sayed Ahmed Hassanein Hussein; Abdalsamd Abdalsatar Ali Aldbaa; Ali Abdelhamid Abdelhady; Ibraheem Atya Hussien Yousif (Cairo : Sayed Ahmed Hassanein Hussein, 2020)
The investigated area located between longitudes 22{u00B0} 25' 243 to 27{u00B0} 47' 50" E and latitudes 31{u00B0} 7' 26" to 31{u00B0} 13' 41" N. The objectives of this study were to assess the land capability using Storie Index and Cervatana model and to assess the land suitability by LUSET and Almagra model. Landsat image, DEM, geological map, field and laboratory analysis were used to create physiographic soil map. Twenty-seven soil profiles were dug and morphologically described to represent all physiographic units. Based on the modified Storie Index, soils were classified into four land capability grades (grade 2, 3, 4 and 5). The Cervatana model classified the investigated soils into three capability classes, S2, S3 and N. Results of Almagra model indicated that 4.71 % of the investigated area is highly suitable (S2) for wheat and citrus, where 14.82 % of the area is S2 for olives. About 31.78 % of the soils is moderately suitable (S3) for wheat and citrus where 52 % are S3 for olives. Based on LUST, about 5.85, 3.73 and 2.11 % of soils are highly suitable (S1) for wheat, cotton and olives respectively. About 31 % of the study area is moderately suitable (S2) for citrus and peach where 63.86 % is S2 for alfalfa and 85 % of the studied area is S2 for wheat. Soil salinity, calcium carbonate, drainage and soil texture were the most common limiting factors in the investigated soils. This study revealed that the MicroLEIS application either Cervatana or Almagra is not recommended to predict land suitability and land capability where the LUSET and Modified Storie index is recommended under Egyptian Circumstances
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Soils Science
Issued also as CD
Keywords: Cervatana; Land Evaluation; Storie Index